Automatic Screen Reader Using JITBIT for Sending Message on WhatsApp Messenger - Alam Rahmatulloh; Faisal Muhammad Dzikry; Rahmi Nur Shofa; Randi Rizal (Politeknik Negeri Cilacap, 2023)
The current sales trend uses more online transaction concepts. The use of digitalization in online transactions and marketing is very important for businesses in increasing sales results to the maximum and on target. One way to increase this is by promoting on social media such as WhatsApp. Limited consumer contact makes it difficult for business actors to carry out promotions, so a database of consumer contacts is needed that can be maximized. In addition, problems in the process of sending manual messages can be overcome by using automatic message-sending actions so that promotions can be carried out automatically and quickly. The sending process is assisted by an